Implementasi Program Kampus Mengajar Angkatan 5 Dalam Meningkatkan Kemampuan Literasi Dan Numerasi Hingga Adaptasi Teknologi Pada SDN Gunungsari I/484 Surabaya - Nala Hikmatul Machmudah; Cholis Hidayati (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
Teaching Campus is a learning channel that provides opportunities for students to study off-campus for one semester in order to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. In this program, students are responsible for assisting the school in the teaching and learning process, technology adaptation, and school administration. In addition, students have the responsibility to improve students' literacy and numeracy as well as increase students' interest in learning. The results of this program are expected to foster students' social sensitivity to help the surrounding community, hone thinking skills in working with groups and teachers, develop character insights and student soft skills.